Pengaruh Latihan Rondo Terhadap Peningkatan Kemampuan First Touch Pemain Sepak Bola Usia Sekolah - Nabila Azzahra; Carsiwan; Mudjihartono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
First touch ability is a fundamental technical skill that determines the quality of ball control and decision-making in soccer players, yet preliminary observations of school-age players at the Trio Jatinangor Football Club revealed that this ability was still suboptimal, so this study aimed to examine the effect of rondo training on improving the first touch ability of school-age soccer players. The study employed a quantitative approach using a pre-experimental one group pretest-posttest design involving 20 players aged 14–16 years selected through purposive sampling, who underwent a rondo training program for 12 sessions, with first touch ability measured using the Bobby Charlton passing test which has been adapted by Rifan and analyzed through descriptive statistics, the Shapiro-Wilk normality test, and the paired samples t-test. The results showed an increase in the mean first touch score from 53.50 at pretest to 72.50 at posttest, with the paired samples t-test yielding a t-value of -8.025 and a significance value (Sig. 2-tailed) of <0.001 (p<0.05). Based on these results, it can be concluded that rondo training has a significant effect on improving the first touch ability of school-age soccer players, so it can be recommended as a training method in basic soccer technique development programs. Keywords: First Touch, Rondo Training, Football, School-Age